2011
DOI: 10.4238/vol10-1gmr927
|View full text |Cite
|
Sign up to set email alerts
|

Investigating paraoxonase-1 gene Q192R and L55M polymorphism in patients with renal cell cancer

Abstract: ABSTRACT. Increased oxidative stress can help promote carcinogenesis, including development of renal cell carcinoma. The enzyme protects low-density lipoproteins from oxidation and can be a factor in this process. PON1 Q192R and L55M paraoxonase gene polymorphisms were assessed in 60 renal cell carcinoma patients and 60 healthy controls. Genotypes were examined by PCR; the restriction enzyme AlwI was used to examine the Q192R polymorphism and Hsp92II for the L55M polymorphism. Significant differences in the PO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
1
12
0
1
Order By: Relevance
“…Lurie and colleagues [119] and Arpaci and colleagues [120] reported conflicting data regarding the impact of the rs662 SNP on the development of ovarian cancer. The G allele of this SNP was significantly more frequent in controls than in cases with renal cell carcinoma [121], which is consistent with the majority of the previously mentioned findings. However, Ozturk and associates [92] demonstrated that carrying this protective allele was associated with an increased risk of bladder cancer, which may be explained by a possible role of PON1 in the carcinogenesis of bladder epithelium and other acidic environments.…”
Section: Other Malignanciessupporting
confidence: 93%
See 1 more Smart Citation
“…Lurie and colleagues [119] and Arpaci and colleagues [120] reported conflicting data regarding the impact of the rs662 SNP on the development of ovarian cancer. The G allele of this SNP was significantly more frequent in controls than in cases with renal cell carcinoma [121], which is consistent with the majority of the previously mentioned findings. However, Ozturk and associates [92] demonstrated that carrying this protective allele was associated with an increased risk of bladder cancer, which may be explained by a possible role of PON1 in the carcinogenesis of bladder epithelium and other acidic environments.…”
Section: Other Malignanciessupporting
confidence: 93%
“…No statistically significant associations were found between the rs854560 SNP and subjects with renal cell carcinoma [121], bladder cancer [92], colorectal carcinoma [125], and lung cancer [122]. De Roos and colleagues [126] established that the mutant AA genotype was a risk factor for the development of non-Hodgkin lymphoma, especially for follicular and T-cell subtypes in non-Hispanic, white subjects.…”
Section: Other Malignanciesmentioning
confidence: 99%
“…Also, serum PON1 and arylesterase activities were reduced in patients with epithelial ovarian cancer [2] and lung cancer [3]. Uyar et al found that Q allele of PON1 was more frequent in renal cancer patients [4], and Antognelli at al. reported that certain PON1 genotypes were prone to increased risk of prostate cancer [5].…”
Section: Altered Expression Levels Of Paraoxonase Enzymes In Cancermentioning
confidence: 99%
“…It was shown that the GPX1 Leu allele was less responsive than the Pro allele during stimulation of the GPX1 enzyme activity by selenium supplementation in vitro (Uyar et al, 2011;Wei et al, 2011). The presence of a more frequent Pro allelle may make FMF patients more vulnerable to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…It has been associated with the detoxification of organophosphates and possibly in the prevention of low-density lipoprotein oxidation (Biasioli et al, 2003). Two major genetic polymorphisms of PON1 have been described due to glutamine or arginine at position 192 (Q/R192) and methionine or leucine at position 55 (L/M) (Uyar et al, 2011). These polymorphisms are associated with difference in serum activities and concentrations of the enzymes (Adkins et al, 1993).…”
Section: Introductionmentioning
confidence: 99%